2006
DOI: 10.1007/s11604-005-1535-z
|View full text |Cite
|
Sign up to set email alerts
|

Change of diffusion anisotropy in patients with acute cerebral infarction using statistical parametric analysis

Abstract: We believe statistical comparison of FA maps to be useful for detecting different regions of diffusion anisotropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…39 However, there have been few studies of ischemic lesions themselves using FA values. Morita and colleagues reported that signiˆcant changes in diŠusion anisotropy were limited to the severely infarcted core of the white matter, 40 and those changes were observed in only 3 patients. Assaf and Pasternak reported apparently limited radiological beneˆts of diŠusion tensor imaging (DTI).…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…39 However, there have been few studies of ischemic lesions themselves using FA values. Morita and colleagues reported that signiˆcant changes in diŠusion anisotropy were limited to the severely infarcted core of the white matter, 40 and those changes were observed in only 3 patients. Assaf and Pasternak reported apparently limited radiological beneˆts of diŠusion tensor imaging (DTI).…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…Although FA has consistently been shown to decrease after stroke as gray and white matter disintegrate (Buffon et al, 2005), some variability in FA has been observed acutely. Decreases (Morita et al, 2006;Zelaya et al, 1999) and increases (Bhagat et al, 2008;Ozsunar et al, 2004) have been observed, and though the exact mechanism of the increase remains unclear, it is possible that perpendicular diffusion is restricted hyperacutely. Recovery of FA values 3 years after stroke has been observed in the internal capsule of patients with upper limb impairments subjected to 30 days of motor training (Stinear et al, 2007).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…Among the various DT parameters, FA has been examined extensively in both human stroke studies and animal models as a potential imaging biomarker ( 8 9 11 17 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ). However, the evolution of FA during hyperacute stroke has not yielded consistent results, with studies reporting both increases and decreases in FA during the initial hours, as well as findings showing no significant changes at all ( 16 25 26 27 28 29 30 31 32 33 ). Nevertheless, our results are in agreement with those of a recent study by Kuo et al ( 11 ) in that rFA was paradoxically elevated in IC during the first hour post-pMCAO, regardless of its cortical or subcortical involvement.…”
Section: Discussionmentioning
confidence: 99%